Bruegel, Caravaggio, van Gogh i inni. Malarskie tematy w późnej twórczości Kazimierza Wierzyńskiego - Ligęza, Wojciech (Przestrzenie Teorii, 2024)
In the late period of Kazimierz Wierzyński’s poetry the poems devoted to paintings are parallel to poems about writers and literature, also about composers and music. Intertextuality of Wierzyński links with reflections about his own biography, consideration about contemporary history and meditations devoted to existential and metaphysical quests. This poet took up the attentive studies upon the world art. Writing about victory of the universal values, he wants to overcome the traumatic experiences of exile. In the history of art Wierzyński searched the areas of rescue. He considered philosophical problems such as right and evil, moment and constancy, life and death. He was interested in actuality of art and universality of anthropological problems in painting expression. In this work the matter of interpretations are the such poems by Wierzyński, as Van Gogh, Caravaggio, Kobiety, które tkają (The Women which are Weaving), Painting.